Small Molecule Derived From Carboxyethylpyrrole Protein Adducts Promotes Angiogenesis in a Mouse Model of Peripheral Arterial Disease. Issue 18 (18th September 2018) - Hou, Luqia; Yang, Guang; Tang, Shibing; Alcazar, Cynthia; Joshi, Prajakta; Strassberg, Zachary; Kim, Michael; Kawamura, Masashi; Woo, Y. Joseph; Shrager, Joseph; Ding, Sheng; Huang, Ngan F.
Abstract : Background: CEP (ω‐[2‐carboxyethyl]pyrrole) protein adducts are the end products of lipid oxidation associated with inflammation and have been implicated in the induction of angiogenesis in pathological conditions such as tissue ischemia. We synthesized small molecules derived from CEP protein adducts and evaluated the angiogenic effect of the CEP analog CEP03 in the setting of peripheral arterial disease. Methods and Results: The angiogenic effect of CEP03 was assessed by in vitro analysis of primary human microvascular endothelial cell proliferation and tubelike formation in Matrigel (Corning). In the presence of CEP03, proliferation of endothelial cells in vitro increased by 27±18% under hypoxic (1% O2 ) conditions, reaching similar levels to that of VEGFA (vascular endothelial growth factor A) stimulation (22±10%), relative to the vehicle control treatment. A similar effect of CEP03 was demonstrated in the increased number of tubelike branches in Matrigel, reaching >70% induction in hypoxia, compared with the vehicle control. The therapeutic potential of CEP03 was further evaluated in a mouse model of peripheral arterial disease by quantification of blood perfusion recovery and capillary density. In the ischemic hind limb, treatment of CEP03 encapsulated within Matrigel significantly enhanced blood perfusion by 2‐fold after 14 days compared with those treated with Matrigel alone. Moreover, these results concurred with histological finding that treatment of CEP03 in Matrigel resulted in a significant increase in microvessel density compared with Matrigel alone. Conclusions: Our data suggest that CEP03 has a profound positive effect on angiogenesis and neovessel formation and thus has therapeutic potential for treatment of peripheral arterial disease.